(untitled) (Journal of the College of Basic Education, 2022)
The research aims to study the different figurative worlds in the narrative text of Adham Sharkawy. He did not follow one world, but his narrative method differed between the real world and the imaginary world. Sharkawy does not work to express his ideas superficially; Rather, he works to mix those images with his ideas and imaginative dimensionsa; In order to demonstrate vibrant images through the use of the image based on rhetorical elements, in which he tries to combine the awareness and the subconscious to produce a different coherent text that carries connotations to be achieved by the writer and broadcasts certain aesthetics from it, and that imagination is a tool that the creator uses and broadcasts in his literary text; To attract the recipient and to make his text more effective, in order to get the text out of monotony, stereotyping, and direct expression that the writer uses in his texts in order to convey an idea. Sharqawi combined the real and imaginary worlds to weave his narrative text, and we will explain this in the corresponding pages.